Assessing ESG Metrics and Their Impact on Sustainable Performance in the Indian Plantation Industry - Usha M, (Journal of Contemporary Research in Management (JCRM), 2024)
The current scenario which emphasizes on the importance of sustainable reporting across various industries has gained great momentum due to which there is a rising trend in considering the environmental, social and governance factors in evaluating important investment decision making. The plantation in India is considered to one of the oldest and is having significant socio-economic and environmental importance. However, the process of adopting and incorporating the ESG factors in this particular sector in the nascent stage. This research aims to critically evaluate and assess the current scenario in the adoption and reporting of ESG factors in the Indian Plantation Sector. It also discusses the sector-specific challenges in ESG factors such as biodiversity loss, deforestation, use of pesticides, payment of reasonable wages to workers, worker health conditions, women’s empowerment, and good governance practices. This research uses descriptive and causal research techniques to collect primary data through structured questionnaires from plantations in South India, particularly in the state of Kerala. The best practices, trends, and gaps in ESG integration have been identified by a number of statistical analyses and their report. An ESG reporting methodology for a particular industry is recommended based on the study in order to address the sector's problems. Each ESG dimension's key performance indicators and implementation recommendations will be included in the ESG reporting framework. The study emphasizes how important ESG reporting is for encouraging openness, ethical investing, and sustainable development in rural and environmentally vulnerable areas.